2005
DOI: 10.1002/cjoc.200591309
|View full text |Cite
|
Sign up to set email alerts
|

Organic Nanotubes Prepared from Chiral Molecules by the Template Method

Abstract: Organic nanotubes from two kinds of chiral molecules, R-di-2-naphthylprolinol (DNP) with an asymmetric carbon atom and R-(+)-1,1'-bi-2-naphthol dimethyl ether (BNDE) with the conformational asymmetry, were prepared by the immersing technique using porous alumina membranes as the template. It was found that the nanotubes from DNP with an asymmetric carbon atom presented the same chirality as the solution with slight red shift of the CD signals upon the formation of the nanotubes, while no well-defined chirality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 37 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…7,8 Yao et al 6,[9][10][11] have synthesized a series of organic nanoparticles by the reprecipitation method and organic nanotubes by the immersing technique using porous alumina membranes as the template, 12 such as, 1,3-diphenyl-5-(2-anthryl)-2-pyrazoline (DAP), 9 1-phenyl-3-((dimethylamino) styryl)-5-((dimethylamino)phenyl)-2-pyrazoline (PDDP), 6 1,3-diphenyl-2-pyrazoline (DP), 10 1,3-diphenyl-5-pyrenyl-2-pyrazoline (DPP) nanoparticles 11 and R-di-2-naphthyl prolinol (DNP) nanotubes. 12 They suggested that the organic nanoparticles also possess significant quantum size effects resembling those of inorganic semiconductors and metals. Jang et al 5 have prepared dye-conducting polymer core-shell composite nanoparticles (pyrene-polypyrrole) using microemulsion micelles as nanoreactors.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Yao et al 6,[9][10][11] have synthesized a series of organic nanoparticles by the reprecipitation method and organic nanotubes by the immersing technique using porous alumina membranes as the template, 12 such as, 1,3-diphenyl-5-(2-anthryl)-2-pyrazoline (DAP), 9 1-phenyl-3-((dimethylamino) styryl)-5-((dimethylamino)phenyl)-2-pyrazoline (PDDP), 6 1,3-diphenyl-2-pyrazoline (DP), 10 1,3-diphenyl-5-pyrenyl-2-pyrazoline (DPP) nanoparticles 11 and R-di-2-naphthyl prolinol (DNP) nanotubes. 12 They suggested that the organic nanoparticles also possess significant quantum size effects resembling those of inorganic semiconductors and metals. Jang et al 5 have prepared dye-conducting polymer core-shell composite nanoparticles (pyrene-polypyrrole) using microemulsion micelles as nanoreactors.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, carbon nanotubes 1 as well as other kinds of nanotubes composed of inorganic compounds, [2][3][4][5] or organic polymers [6][7][8][9] have been synthesized. And subsequently biofunctionalized nanotubes have been particularly focused on because of their potential applications to biosensors, [10][11][12] bioseparations and biocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…We have achieved high‐quality SERS spectra of the chiral molecule ( R )‐di‐2‐naphthylprolinol (DNP) on the Ag‐NP‐modified Ag electrode, using an ultradilute solution at a concentration of 10 −12 M . It should be mentioned that DNP is an interesting molecule whose intramolecular interactions of the π–π type or the hydrogen bonds may induce a change of the dihedral angle between the two naphthalene rings in the molecule12, 13 and hence might affect the chirality of the molecule to a certain degree 14…”
Section: Introductionmentioning
confidence: 99%